Culturally responsive teaching pedagogy as a form of knowledge ecology: A systematic literature review of EFL classrooms - Nabila Yumna Istiadi; Yuliati Yuliati (Universitas Islam Sultan Agung, 2026)
The pursuit of equity and social justice in higher education demands pedagogical approaches that transcend Western-centric traditions and legitimise diverse cultural epistemologies. This study examines Culturally Responsive Teaching (CRT) specifically in the Indonesian EFL context and intends to examine CRT as a pedagogical strategy and a way to problematise epistemological assumptions. Guided by the PRISMA 2020 framework and analysed through Critical Discourse Analysis (CDA) combined with document analysis), this research critically examines 22 documents. The findings indicate that, although CRT is recognised in national initiatives such as the Emancipated Curriculum and Emancipated Learning, its practical implementation remains uneven and largely superficial. At the classroom level, educators attempt to integrate indigenous knowledge, cultural identities, and local wisdom into English language teaching; however, these efforts are constrained by rigid, exam-driven curricula, limited professional support, and the pervasive influence of global English standards. The tension between internationalisation and localisation illustrates both the challenges and opportunities for CRT in reshaping Indonesian EFL education. Theoretically, CRT is positioned as a decolonial stance that resists epistemic hegemony while advancing epistemic justice by legitimising the ecology of knowledge. Practically, the study emphasises the urgency of aligning policies with CRT principles, expanding teacher training, and developing culturally sustaining instructional resources. By situating CRT at the nexus of social justice, decolonization, and global competence, this study contributes to global debates on inclusive and transformative education, highlighting its significance for the Global South and beyond.